Facial paresis: a worrying event related to labial herpes simplex and periocular botulinum toxin a injection - Faga, Angela; Scevola, Silvia; Dalla Toffola, Elena; Nicoletti, Giovanni (Aesthetic Medicine, 2023)
The Authors report on a case of facial paresis following reactivation of labial Herpes simplex in a 59 years woman treated with sequential periocular BoNTA injection and blepharoplasty. A mild palsy occurred on the whole right hemiface 12 days after upper blepharoplasty, 22 days after BoNTA injection (40 U) in the periorbital area and in the glabella. The patient was treated with Acyclovir for 5 days and with oral B complex vitamins for 12 weeks. The symptoms slowly recovered in 4 months. Facial paresis might have been simply triggered by an invasive treatment related inflammatory reaction. Nevertheless, the Herpes virus might have promoted the anterograde diffusion of the toxin, previously migrated from the site of injection to the facial nucleus through a retrograde pathway. The Authors suggest Acyclovir prophylaxis in patients affected by recent or recurrent forms of Herpes simplex infection when planning BoNTA injection in the face.